Pengaruh Modal Inti Terhadap Profitabilitas Dan Kinerja Perbankan (Studi Pada Bank Syariah Di Indonesia) - Kristiningsih - Kristiningsih; Ruswiati Ruswiati (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Background - The growth potential of sharia banking business in Indonesia is increasing, so it is important to evaluate the performance of sharia banking. Aim - This study aims to examine the effect of core capital on the profitability and performance of Islamic Commercial Banks listed on the Indonesia Stock Exchange. This research is expected to provide input in financial knowledge, especially in the field of evaluating bank financial performance and the factors that influence it. Design/ Methodology/ Approach - The research object is 12 Islamic banks in Indonesia. The data is taken from the financial statements of each Islamic bank from 2015 to 2018. Hypothesis testing is carried out using a structural equation model with the WARP PLS program. Results and Discussion – The results show that core capital has a significant effect on profitability, as well as profitability has a significant effect on core capital. The results also show that core capital has no effect on performance and performance has no significant effect on core capital. The results showed that profitability had no effect on performance. Conclusion - The results of this study conclude that of the five hypotheses proposed only two are accepted, namely core capital has a significant effect on profitability, and vice versa profitability also has a significant effect on core capital. This study produces evidence that core capital has no significant effect on the performance of Islamic banks. Likewise, it turns out that profitability also does not significantly affect the performance of Islamic banks, but on the contrary, the performance of Islamic banks has no significant effect on profitability. Research implications - for the Islamic banking business, this research can provide input on how to measure the performance of Islamic banks through the profitability and core capital of Islamic banks. The object of research is 12 Islamic banks in. Limitations of the study - The research was carried out during the period when Islamic banks in Indonesia had not been merged